Thickness determination of gold layer on pre‐Columbian objects and a gilding frame, combining pXRF and PLS regression. (27th September 2016) - Lopes, Fabio; Melquiades, Fabio Luiz; Appoloni, Carlos Roberto; Cesareo, Roberto; Rizzutto, Marcia; Silva, Tiago F.
Abstract : In conservation, restoration and characterization studies of art and archaeological objects, the improvement of analytical techniques is a tendency. X‐ray fluorescence (XRF) is a versatile technique, and it has been widely used in the last decades for characterization of a great variety of materials (metals, glass, paints, inks, ceramics, etc.) applied to cultural heritage studies. Besides the chemical composition, it is possible to infer the layer thickness through XRF, enabling a general knowledge of the manufacturing techniques implemented by the culture of origin, as well as the association with the technological level reached for the production of each kind of artefact. The aim of this study is to introduce an alternative way for gold thickness determination of coatings in cultural heritage objects, combining portable XRF data and partial least square regression. As a case of study, we present the use of this methodology in portable XRF measurements performed in situ on a gilding frame in Brazil and in two pre‐Columbian artefacts from Chavin culture in Peru. Gold layers with thicknesses determined by Rutherford backscattering spectrometry (RBS) were used as standards to perform a calibration model and to check the methodology before its application to unknown artefacts. Copyright © 2016 John Wiley & Sons, Ltd.